Evaluating partial and simultaneous effects of logical-mathematical, visual-spatial, and intrapersonal intelligence on prospective primary teachers’ problem solving - Ika Febriana Wati; Pujiriyanto Pujiriyanto (Universitas Islam Negeri (UIN) Mataram, 2022)
[English]: Problem-solving is the heart of mathematics learning that can be influenced by intelligence. Logical-mathematical, visual-spatial, and intrapersonal intelligence have possible effects on problem-solving. This ex post facto quantitative research aims to evaluate the effect of the three intelligence on the ability of prospective primary teachers (PPT) to solve mathematical problems partially and simultaneously. The research sample (n=207) was selected through proportional stratified random sampling using the Slovin formula. Data were collected through a test and questionnaire that had been tested for content and construct validity as well as construct and composite reliability. Data prerequisite tests include tests for normality, linearity, multicollinearity, and heteroscedasticity. Hypothesis testing is done through a multiple regression test. The results show that logical-mathematical, visual-spatial, and intrapersonal intelligence simultaneously have a significant effect on PPTs’ mathematical problem-solving with a large effect of 30.3%. Partially, intrapersonal intelligence does not have a significant effect on problem-solving ability. [Bahasa]: Pemecahan masalah merupakan jantung pembelajaran matematika yang bisa dipengaruhi oleh faktor kecerdasan. Jenis kecerdasan yang berpotensi memiliki pengaruh adalah logis-matematis, spasial-visual, dan intrapersonal. Penelitian kuantitatif ex post facto ini bertujuan untuk menguji pengaruh dari ketiga kecerdasan tersebut terhadap kemampuan pemecahan masalah matematis secara parsial maupun simultan. Sebanyak 207 mahasiswa sebagai sampel penelitian dipilih melalui proportional stratified random sampling menggunakan rumus Slovin. Data dikumpulkan melalui tes dan kuesioner yang sudah di uji validitas isi dan konstruk serta reliabilitas konstruk dan komposit. Uji prasyarat data meliputi uji normalitas, linearitas, multikolinearitas, dan heteroskedastisitas. Uji hipotesis dilakukan melalui uji regresi berganda. Hasil penelitian menunjukkan bahwa kecerdasan logis-matematis, spasial-visual, dan intrapersonal secara simultan berpengaruh signifikan terhadap kemampuan pemecahan masalah matematis dengan besar pengaruh 30,3%. Sedangkan secara parsial hanya kecerdasan intrapersonal yang tidak memiliki pengaruh signifikan terhadap kemampuan pemecahan masalah matematis.